2017
DOI: 10.1108/aaaj-12-2014-1887
|View full text |Cite
|
Sign up to set email alerts
|

From “mad men” to “math men”

Abstract: Purpose-We study how communication agencies became important sites for the rise of measurement expertise in the government of consumer conduct following the development of online consumption. Our examination focuses on the processes by which digital measurement developed (within the agencies) as a new legitimate form of expertise, able to produce relevant and detailed knowledge about the government of web-users. Design/methodology/approach-We carried out a field examination in France, predicated on 100 intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 59 publications
1
6
0
2
Order By: Relevance
“…The conservationists' experiences reveal how financialization has gradually become one of the only imaginable ways to govern our lives (Kurunmäki et al 2016). Such findings evoke similar observations in corporate social responsibility, where social and environmental actions are often justified with a market rationale (Malsch 2013), or in studies of the development of accounting practices without accountants (Viale et al 2017). These commonalities may indicate a broader societal shift that would benefit from further research, notably to understand better standard financialization technologies' role (or absence thereof) and their human carriers—such as consultants, accountants, or standard setters.…”
Section: Discussionsupporting
confidence: 78%
“…The conservationists' experiences reveal how financialization has gradually become one of the only imaginable ways to govern our lives (Kurunmäki et al 2016). Such findings evoke similar observations in corporate social responsibility, where social and environmental actions are often justified with a market rationale (Malsch 2013), or in studies of the development of accounting practices without accountants (Viale et al 2017). These commonalities may indicate a broader societal shift that would benefit from further research, notably to understand better standard financialization technologies' role (or absence thereof) and their human carriers—such as consultants, accountants, or standard setters.…”
Section: Discussionsupporting
confidence: 78%
“…Extant literature has highlighted the growing significance of measuring the outcomes of activities in relation to digitalised users (Hoffman and Fodor, 2010;Katsikeas et al, 2016;Kumar et al, 2013). Discussions around measurements of marketing activities have increased regarding social media work (Luo et al, 2013;Viale et al, 2017). Our study offers insights concerning this central capability, since our field work showed data analytics is centralised as the underlying rationale of work practices related to digital technologies.…”
Section: Discussionmentioning
confidence: 76%
“…Discussions around measurements of marketing activities have increased regarding social media work (Luo et al. , 2013; Viale et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with the notion of expertise derived from professionalism, this operates to implement “specialized truths and rare powers” (Miller and Rose, 1990, p. 2). In this way, accounting conforms to the definition of an intellectual technology (Miller and Rose, 1990), and decisions are deferred to the judgement of “experts” (Viale et al , 2017).…”
Section: Socio-technical Theory and Close-reading Approachmentioning
confidence: 99%